2020
DOI: 10.1063/5.0020109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alternating current electric field poling on piezoelectric and dielectric properties of Pb(In1/2Nb1/2)O3–Pb(Mg1/3Nb2/3)O3–PbTiO3 ferroelectric crystals

Abstract: Compared with the state-of-the-art Pb(Zr,Ti)O3 ceramics, relaxor-PbTiO3 (PT) based ferroelectric single crystals possess much higher piezoelectricity, thus receiving considerable attention from the ferroelectric community. Recently, it was found that the alternating current electric field poling (AC-poling) could further improve the piezoelectricity of [001]-poled rhombohedral (R) relaxor-PT single crystals. In this work, we investigated the domain structures and electromechanical properties of alternating cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…The domain walls almost disappeared, suggesting the emergence of a monodomain state. Our experimental results are consistent with the theorical calculation results reported by Xu et al [2,3,18,19]. Therefore, we propose that the decrease of domain walls density and ordered domain structure is beneficial to improve the crystal transmittance.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The domain walls almost disappeared, suggesting the emergence of a monodomain state. Our experimental results are consistent with the theorical calculation results reported by Xu et al [2,3,18,19]. Therefore, we propose that the decrease of domain walls density and ordered domain structure is beneficial to improve the crystal transmittance.…”
Section: Resultssupporting
confidence: 92%
“…After the crystal was poled using the DC electric field, the domain size increased and the discontinuous domains showed an obvious decrease (Figure 4b). According to a previous report by Liu [18], this is a typical '4R' engineering domain configuration with 71 • and 109 • domain walls. For the AC-poled sample in Figure 4c, the domain configuration underwent amazing changes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that AC-poling can enhance both the dielectric and piezoelectric performance for relaxor-PT crystals. [26][27][28][29][30][31][32][33] Thus, it is expected that the piezoelectric properties for textured ceramics can be enhanced by the AC-poling. Figure 6A shows the P-E hysteresis loops of textured PMN-28PT ceramic with 1 vol.% BT templates from 1st to 10th cycle of AC electric field, and it can be seen that the E c significantly decreases from 1st to 3rd cycle of AC electric field, while it becomes stable from 4th to 10th cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many studies have shown that the technique of alternating current electric field poling (AC-poling) can enhance both the dielectric and piezoelectric performance of relaxor-PT crystals by 20-50%, when compared to the direct current electric field poling (DC-poling). [26][27][28][29][30][31][32][33] Due to the similarity between single crystals and textured ceramics, it is also necessary to investigate the impact of ACpoling on the dielectric and piezoelectric performances of textured ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with PMN-PT crystals, the piezoelectric and dielectric properties of 0.66PIN-0.34PT crystals aer ACP are more dependent on frequency. The previous work revealed that the piezoelectric performances of PMN-PT and PIN-PMN-PT crystals can be signicantly improved using low frequency ACP, 29,30 22 The ACP process can reduce the energy required for domain rotation, which makes domain rotation easy. 28 The poling cycle is the process of the reduction of the energy required for domain rotation.…”
Section: Poling Conditionsmentioning
confidence: 99%